2014
DOI: 10.1142/s2010135x14500088
|View full text |Cite
|
Sign up to set email alerts
|

Meso-design of heterogeneous dielectric material systems: Structure property relationships

Abstract: Heterogeneous materials are inherently dielectric, and charge distribution and transport in such materials involves complex local fields and polarizations that are remarkably sensitive to morphology and the interaction of conduction and permittivity. Trial and error design of such material systems is time consuming and expensive, and often ineffectual. However, heterogeneous materials are essential for energy conversion and storage, and they have become the foundation for major advances in the performance of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In composite material systems, there are many initial interfaces, and as material damage develops, many new internal interfaces and surfaces develop. We have shown that each of these surfaces and interfaces is a location of charge accumulation (and possible motion), and that there is a corresponding change in the local electric field as one passes from one phase to another [1,2]. Moreover, we have found that the amount of local charge and local field can be calculated from first principles if the properties and morphology of the local phases are known [2].…”
Section: Introduction: Dielectric Properties Of Composite Materialsmentioning
confidence: 88%
See 2 more Smart Citations
“…In composite material systems, there are many initial interfaces, and as material damage develops, many new internal interfaces and surfaces develop. We have shown that each of these surfaces and interfaces is a location of charge accumulation (and possible motion), and that there is a corresponding change in the local electric field as one passes from one phase to another [1,2]. Moreover, we have found that the amount of local charge and local field can be calculated from first principles if the properties and morphology of the local phases are known [2].…”
Section: Introduction: Dielectric Properties Of Composite Materialsmentioning
confidence: 88%
“…The top and bottom of the domain were periodic boundaries free of applied charge. In order to accurately predict the capacitance, it is crucial to satisfy the discontinuous interfacial conditions at the interface between two different materials and to accurately account for the interactions between particles, fields, and boundaries, a capability that has been extensively validated for our algorithm [1,2]. The relative static permittivity of the matrix was set to 5 and its ε``value is set to 0.01.…”
Section: Wwwzamm-journalorgmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of previous publications, we have applied equation (3) to some of the complex microstructures illustrated in Figure 1 at the conformal level, and have included electrochemical effects on the resulting flux terms shown in that equation. However, in this publication, we are only concerned with constructing a predictive method for time dependent electric charge distribution (including surface charge) in heterogeneous materials at the fundamental level, and the validation of such a method (Liu 2012;Liu 2011a;Reifsnider et al 2013;Baker et al 2014;Liu 2011b;Raihan et al 2014). Therefore, without loss of generality for the present discussion, we neglect all source terms and concern ourselves with the following simplified version of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, during its service life, the material interface is exposed to numerous variations induced by environmental changes. The charge storage usually occurs at the interfaces and defects of the material [4,5]. Interfacial polarization occurs at the interface, resulting in the dielectric relaxation of the heterogeneous material which enables the determination of the structure and electrical properties of the material.…”
Section: Bbds Of Composite Materials Systemmentioning
confidence: 99%